HUBUNGAN PENGETAHUAN, PEMAHAMAN PERATURAN PAJAK, SANKSI PAJAK, KEMAUAN MEMBAYAR PAJAK TERHADAP TINGKAT KEPATUHAN WPOP (Studi Kasus di KPP Jakarta Matraman) - Seriang, Filomena Sinar (Buletin Ekonomi, 2018)
The obyektive of this research was to determine the relationship of knowledge and understanding regulations of taxation, tax sanctions, and willingness to pay taxes with tax compliance at KPP Jakarta Matraman. Test used validity and reliability, test hypothesis using correlation of spearman, kruskal wallis, mann whitney.The results of the research through the Spearman approach show the significant relation between knowledge and understand of tax regulations (X1) with the level of taxpayer compliance (Y) of 0.643. It is also known significant relations between tax sanctions (X2) and tax compliance (Y) of 0.752. Furthermore, the significant relations between the willing pay taxes (X3) and the level of taxpayer compliance (Y) of 0.682. Based on the Kruskal Wallis test, it is known that X1, X2, X3 has significant effect on Y. Based on the Mann Whitney test, it is known that each variable X has significant effect on Y. Keyword : knowledge, understand of tax regulations, tax sanctions, willing pay taxes athe, level of taxpayer compliance.